2012
DOI: 10.1002/masy.201200005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Mutant Apomyoglobin Association

Abstract: Association of protein molecules in human tissues underlies many diseases, which brings it in the focus of numerous studies. Previous reports described amyloid formation with the unfolded protein state taken as the starting point. Here, we present kinetics of protein aggregation starting from the protein native state and with consideration of its structural stability. We constructed mutant forms of apomyoglobin (apoMb) and investigated them by light scattering, small-angle Xray scattering (SAXS), transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The tendency of proteins to aggregation complicated the performance of SAXS experiments; however, some information on their conformation in aggregates can be obtained, as was demonstrated by us for myoglobin [13]. We investigated conformation of oligomers plotting dependence logI-logQ where; I—intensity, Q—module of scattering vector.…”
Section: Resultsmentioning
confidence: 99%
“…The tendency of proteins to aggregation complicated the performance of SAXS experiments; however, some information on their conformation in aggregates can be obtained, as was demonstrated by us for myoglobin [13]. We investigated conformation of oligomers plotting dependence logI-logQ where; I—intensity, Q—module of scattering vector.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that aggregation of WT sw ApoMb and its mutants is over in less than 24 h, and all recorded parameters (ThT fluorescence intensity, shape of FTIR spectra, and aggregate morphology) reach a plateau (37,64). However, during this time, some studied proteins do not completely convert to aggregates.…”
Section: Aggregation Propensities Of Wt Sw Apo and Its Mutantsmentioning
confidence: 89%